Hydrolysis of residual starch from sago pith residue and its fermentation to bioethanol - Nurul Adela Bukhari; Soh, Kheang Loh; Nasrin Abu Bakar; Maizan Ismail (Penerbit Universiti Kebangsaan Malaysia, 2017)
Utilisation of sago pith residue (SPR) for fermentable sugar production using both acid and enzymatic hydrolysis was studied. In acid hydrolysis, the effect of solid and acid concentrations, temperature and reaction time was optimised. The effect of enzyme dosage was studied on enzymatic hydrolysis of SPR. Higher yield and conversion of 0.73 g g-1 (96% conversion) was achieved by treating 6% (w v-1) of SPR with 1% (v v-1) H2SO4 at 125°C for 90 min as compared to 0.61 g g-1 (79% conversion) using 40 U g-1 biomass of Aspergillus niger amyloglucosidase incubated at 60°C and pH4 for 48 h. The fermentation of acid hydrolysate of SPR demonstrated that high ethanol yield of 98% can be achieved without supplementation of nitrogen and nutrients. The complete process showed that 470 L of bioethanol could be produced from 1 tonne of SPR. This figure makes SPR an ideal raw material for bio-conversion into bioethanol or other value-added products.